Sholat dhuha sebagai center of excellent dalam menggapai prestasi siswa di MTs Almaarif 02 Singasari - A'yuninah, Kholidah Qurrota (Maliki Interdisciplinary Journal, 2024)
School is a place to educate the nation's generation to make them intelligent and successful people in facing the future, even though schools are madrosatu tsaniyah but schools have an important role in educating every process of child development, starting from knowledge education to character education where this character education will to make students obey the rules in social and religious life by always obeying the teachings of the Islamic religion wherever and whenever they are and abandoning all actions prohibited by Allah SWT. The education that is always carried out in this school is to always apply an attitude of religiosity by implementing the Dhuha Prayer every day which is held at 06.30-07.00 in the MTS school yard. The implementation of the Duha prayer is expected to be able to provide elements of the community in the school to become someone who has sustenance whatever it is so that it is always carried out according to the prayer after the Duha prayer, so the implementation of the Duha prayer can have many benefits among students, namely making students have a lot of achievements. both academic achievements and non-academic achievements and recently the MTS school has won many championships in taekwondo competitions, this school won around 5 medals, from the achievements achieved, this school believes that the priority of the Duha prayer, namely having a smooth fortune, is indeed true.